Pengaruh Media Edukasi Nutri Case ULTAJAS (Ular Tangga Jajanan Sehat) terhadap Pengetahuan dan Sikap Konsumsi Jajanan Sehat Siswa Kelas V di SDN 101866 Batang Kuis: The Effect Of Nutri Case Education Media On The Knowledge And Attitude Of Consuming Healthy Snacks Class V At SDN 101866 Batang Kuis - Dewi Syahfitri; Fitri Dian Nila Sari; Siti Nurlani; Chatrine Virginia Tamara (UNIVERSITAS NGUDI WALUYO, 2025)
School children are one of the groups of snack food connoisseurs, the habit of eating unhealthy and unnutritious snacks has a bad impact on health, one of which is diarrhea causing a lack of fluids. By consuming healthy, safe and nutritious snack food, it can meet nutritional needs for the growth and development process of children. This study aims to: Determine the influence of nutri case educational media on knowledge, attitudes and interactions of nutri case educational media for the selection and consumption of healthy snacks for grade V students of SDN 101866 Batang Kuis. This study uses a quantitative research method with a quasi-experimental design (one-group pre-test - post-test design). Methods and Techniques This research uses data collection, namely the Likert scale questionnaire instrument and data analysis techniques, namely the Chi Square test, and the Anova Multivariate test. The results of the study showed that: with the Chi Square test, there was an influence of nutri case educational media on knowledge of 0.000 and P-Value<0.05, in addition, the results of the analysis showed that there was no influence of nutri case educational media on attitudes of 0.778 and P-Value>0.05, In the Multivariate Anova test, the results were obtained that there was an influence of nutri case educational media on knowledge and attitudes for the selection and consumption of healthy snacks with the results of Wilks' Lambda having an F-count value of 13.497 with a significance of 0.000<0.05, which means that there is an influence between nutri case educational media together on the knowledge and attitude of healthy snack consumption of grade V students of SDN 101866 Batang Kuis. ABSTRAK Anak sekolah menjadi salah satu kelompok penikmat makanan jajanan, kebiasaan makan jajanan yang tidak sehat dan tidak bergizi berdampak buruk bagi kesehatan salah satunya diare menyebabkan kekurangan cairan. Mengkonsumsi makanan jajanan yang sehat, aman dan bergizi dapat mencukupi kebutuhan nutrisi untuk proses pertumbuhan dan perkembangan anak. Penelitian ini bertujuan untuk: Mengetahui pengaruh media edukasi nutri case terhadap pengetahuan, sikap serta interaksi media edukasi nutri case untuk pemilihan dan konsumsi jajanan sehat siswa kelas V SDN 101866 Batang Kuis. Penelitian ini menggunakan metode penelitian kuantitatif dengan desain quasi eksperiment (one-group pre-test - post-test design). Metode dan Teknik Penelitian ini menggunakan pengumpulan data yaitu intrumen angket skala likert dan teknik analisis data yaitu uji Chi Square, serta uji Multivariate Anova. Hasil penelitian menunjukkan bahwa: dengan uji Chi Square terdapat pengaruh media edukasi nutri case terhadap pengetahuan sebesar 0,000 dan P-Value<0,05, selain itu hasil analisis menunjukkan bahwa tidak terdapat pengaruh media edukasi nutri case terhadap sikap sebesar 0,778 dan P-Value>0,05, Pada uji Multivariate Anova didapatkan hasil bahwa terdapat pengaruh media edukasi nutri case terhadap pengetahuan dan sikap untuk pemilihan dan konsumsi jajanan sehat ada pengaruh antara media edukasi nutri case secara bersama terhadap pengetahuan dan sikap konsumsi jajanan sehat siswa kelas V SDN 101866 Batang Kuis.